Cultivating Religious Values Through the Habit of Smiling, Greeting, and Saluting in Schools - Nasution, Ahmad Jailani; Nurdiyanto, Nurdiyanto; Suhartini, Andewi; Basri, Hasan; Habibburrohman, Habibburrohman (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This study aims to explore the implementation of Smile, Greet, Salute Habituation as a religious behavior in the environment of Madrasah Ibtidaiyah Negeri (MIN) 7 Tapanuli Tengah students. The research method used is descriptive research with a qualitative approach. Data were collected through participatory observation, interviews, and analysis of related documents. The results showed that the habituation of 3S at MIN 7 Tapanuli Tengah has had a positive impact in shaping the religious behavior of students. The existence of a supportive school policy and active participation of students in the practice of 3S can create a friendly environment, and mutual respect, and strengthen religious values. The implications of this research can be a reference for other educational institutions in developing inclusive religious practices at the elementary school level.Penelitian ini bertujuan untuk mengeksplorasi implementasi Pembiasaan Senyum, Sapa, Salam (3S) sebagai perilaku keberagamaan di lingkungan peserta didik Madrasah Ibtidaiyah Negeri (MIN) 7 Tapanuli Tengah. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Data dikumpulkan melalui observasi partisipatif, wawancara, dan analisis dokumen terkait. Hasil penelitian menunjukkan bahwa pembiasaan 3S di MIN 7 Tapanuli Tengah telah memberikan dampak positif dalam membentuk perilaku keberagamaan peserta didik. Adanya kebijakan sekolah yang mendukung dan partisipasi aktif peserta didik dalam praktik 3S mampu menciptakan lingkungan yang ramah, saling menghargai, dan memperkuat nilai-nilai keberagamaan. Implikasi dari penelitian ini dapat menjadi acuan bagi institusi pendidikan lain dalam mengembangkan praktik keberagamaan yang inklusif di tingkat sekolah dasar.Â